Effectiveness and Challenges of Restorative Justice in Resolving Domestic Violence Cases: An Empirical Study at the Batam City Prosecutor’s Office - Siti Aisyah; Ampuan Situmeang; Hari Sutra Disemadi (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2025)
Domestic violence remains a pervasive social and legal issue in Indonesia, particularly in Batam City, despite existing legal frameworks. This study aims to analyze the effectiveness of resolving domestic violence cases through restorative justice at the Batam City Prosecutor’s Office and to identify factors influencing its implementation. Employing an empirical legal research method with a juridical-sociological approach, data were collected through interviews, observations, and document analysis. The results reveal that while restorative justice provides a humane and efficient alternative to conventional prosecution—prioritizing victim recovery, offender accountability, and the restoration of social harmony—its application faces challenges. These include limited regulatory authority, punitive mindsets among law enforcement, and low public awareness. However, supporting factors such as an established legal basis, positive prosecutorial attitudes, and community involvement contribute to its success. The study concludes that restorative justice is a viable, progressive approach to addressing domestic violence cases. Sustainable implementation requires regulatory refinement, professional training, and cultural shifts toward restorative principles.